ANALISIS PERAN GURU SEBAGAI MOTIVATOR DALAM MEMBENTUK SIKAP BELAJAR SISWA KELAS V DI MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN TAHUN 2025 - Ibnu, Ziba; Setiabudi, Dede Indra; Susiawati, Iis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Teachers play a crucial role not only in delivering knowledge but also in motivating students to develop positive learning attitudes. This study aims to analyze the teacher’s role as a motivator in shaping the learning attitudes of fifth-grade students at Madrasah Ibtidaiyah Ma’had Al-Zaytun in 2025. Using a qualitative descriptive method, data were collected through observation, interviews, and documentation involving three homeroom teachers and nine students selected purposively. The results show that teachers encourage students’ learning motivation through verbal support, rewards, varied teaching methods, and personal approaches, as well as by creating a comfortable and engaging classroom atmosphere. These efforts foster discipline, enthusiasm, responsibility, and intrinsic motivation among students. The study also found that teacher creativity, adequate facilities, and strong emotional connections between teachers and students support this motivational role, while challenges include differences in student characters and limited individual attention. Overall, the teacher’s role as a motivator significantly contributes to building students’ positive learning attitudes and enhancing the overall quality of learning at the madrasah.